College Algebra (6th Edition)

Published by Pearson
ISBN 10: 0-32178-228-3
ISBN 13: 978-0-32178-228-1

Chapter P - Prerequisites: Fundamental Concepts of Algebra - Exercise Set P.4: 55



Work Step by Step

$$(x-3)^3$$ $$=(x-3)(x-3)(x-3)$$ $$=(x-3)[(x\times x)+(x\times (-3))+(-3\times x)+(-3\times (-3))]$$ $$=(x-3)(x^2-3x-3x+9)$$ $$=(x-3)(x^2-6x+9)$$ $$=(x\times x^2)+(x\times (-6x))+(x\times 9)+(-3\times x^2)+(-3\times (-6x))+(-3\times 9)$$ $$=x^3-6x^2+9x-3x^2+18x-27$$ $$=x^3-9x^2+27x-27$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.